2015
DOI: 10.1136/neurintsurg-2015-011669
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of intracranial aneurysms using the Pipeline Flex embolization device: a case series of 30 consecutive patients

Abstract: The Pipeline Flex embolization device allows more precise and controlled deployment than the first-generation device. The number of devices and the complication rate during the learning curve are lower than reported with the first-generation PED. The new delivery system and the resheathing maneuvers do not seem to increase the intraprocedural complication rate in comparison with the first-generation PED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 16 publications
3
27
1
Order By: Relevance
“…According to these studies, the morbidity and mortality (M & M) rates were 5.6 and 8.4%, respectively, and the incidence of ischemic complications was 4.7%. In the two reports concerning the use of the Flex published to date, 5,6) although the number of cases is still insufficient, the M & M rate and incidence of ischemic complications were 0 and 6.7%, respectively, comparing favorably with the results using the classic type. While data concerning the occlusion rate or delayed complications by a long-term follow-up after treatment using the Flex are not available because of the short history of the use of the device, improvements in the results are expected from the reduced risk of branch occlusion due to improved apposition and rupture prevention by the concomitant use of coils for large parasellar aneurysms, 5) which was rarely performed in the age of the classic type.…”
Section: Comparison Of Clinical Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…According to these studies, the morbidity and mortality (M & M) rates were 5.6 and 8.4%, respectively, and the incidence of ischemic complications was 4.7%. In the two reports concerning the use of the Flex published to date, 5,6) although the number of cases is still insufficient, the M & M rate and incidence of ischemic complications were 0 and 6.7%, respectively, comparing favorably with the results using the classic type. While data concerning the occlusion rate or delayed complications by a long-term follow-up after treatment using the Flex are not available because of the short history of the use of the device, improvements in the results are expected from the reduced risk of branch occlusion due to improved apposition and rupture prevention by the concomitant use of coils for large parasellar aneurysms, 5) which was rarely performed in the age of the classic type.…”
Section: Comparison Of Clinical Resultssupporting
confidence: 56%
“…By exploiting these advantages, recapture or resheath are performed in about half of the reported cases. 5,6) Also, while 14.3% of the stents had to be removed in the series using the classic type reported by Lin et al, 9) no case of removal was reported by Pereira et al, 5) using the Flex. Also, because of the improvement in the delivery wire, in particular, control at curved parts was facilitated, and situations that require adjunctive techniques as mentioned above have decreased.…”
Section: Comparison Of Clinical Resultsmentioning
confidence: 99%
“…Concerning complications of Pipeline placement, the morbidity and mortality were 5.6% and 8.4%, respectively, and the incidence of ischemic complications was 4.7%, in PUFs 1) and InterPED, 8) in which the Pipeline Classic was used, but the morbidity and mortality were improved to 0% and 6.7%, respectively, in recent studies using the Pipeline Flex. 3,4) However, despite the improvements in the device, strong resistance is felt in pushing the delivery wire, making the deployment of the PED difficult in not a few instances. According to our experience, the greatest resistance is felt in expanding the tip of the PED and releasing the protective sleeves, and we have the impression that the resistance is stronger as the PED is larger and longer and as the proximal portion of the vessel in which the device is placed is more tortuous.…”
Section: Discussionmentioning
confidence: 99%
“…With increases in cases treated using the Pipeline Flex, reports of its safety and efficacy are also increasing. 3,4) However, technical problems may arise in its clinical use, but reports concerning technical tips are scarce. We encountered a case of left ICA-cavernous portion (cav) aneurysm in which the resistance to the delivery wire in the microcatheter was so strong that the deployment of the PED was difficult, but the device could be deployed after releasing the polytetrafluoroethylene (PTFE) protective sleeves ex vivo.…”
Section: Introductionmentioning
confidence: 99%
“…2) are two of the more common adverse technical events reported with FDS [26,29,60,82,[86][87][88][89][90]. Prolapse of an FDS into the aneurysm sac has also been reported with different frequencies [59,86,88,91].…”
Section: Thromboembolic and Ischemic Complicationsmentioning
confidence: 99%